The labor market impact of Covid-19 on Asian Americans - Chris de Mena; Suvy Qin; Jing Zhang (Federal Reserve Bank of Chicago, 2023)
Asian Americans faced a disproportionately larger surge in unemployment rates than other racial and ethnic groups during the Covid-19 pandemic. While existing literature typically examines labor demand channels to explain this, we instead explore a labor supply channel. Our hypothesis is that Asian Americans are more cautious about Covid-19 infections and thus more selective about job opportunities, contributing to their higher unemployment rate than other groups. Analysis of cellphone data during the pandemic indicates that non-work mobility significantly decreased in areas with larger Asian populations, supporting our hypothesis.
Keywords: J2; J7; I0; 330; Employment; Employment Creation; Human Capital; Retirement; Labor Discrimination; Labor Inequality; Labor Market Data; Health; Health Data; Health: General; Demand and Supply of Labor; Health; Education; and Welfare